KEPLER’S ORBITAL MOTION EXAMINED IN COMPARISON WITH THE METHODS OF MECHANICS DEVELOPED BY STANESCU AND TABACU - STANISŁAW OLSZEWSKI (TASK Quarterly, 2012)
A new method developed by Stanescu and Tabacu to study the mechanics of a particle moving along a definite curve is compared with the well-known approach applied in calculating the Kepler’s orbital motion. A particular effect of the rate of change of the kinetic energy of a body with respect to the change of a parameter defining the body position on the orbit is examined as an example.